Vibration damping material

By using the combination of foamed olefin polymer and the constraint layer, the follow-up problem of vibration control material on uneven or curved surfaces is solved, and a better vibration suppression effect is achieved.

JP7627577B2Active Publication Date: 2025-02-06MITSUI CHEMICALS INC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021023718
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-17
Publication Date
2025-02-06
Estimated Expiration
2041-02-17

AI Technical Summary

Technical Problem

When existing vibration control materials adhere to the surface, it is difficult to effectively follow the surface with uneven or curved surfaces, resulting in poor vibration suppression effect.

Method used

The vibration control material formed by a resin layer made of foamed olefin polymer, combined with a constraint layer composed of metal plates, metal mesh, fiber reinforced resin layer or glass cloth, has one or more loss factor tanδ peaks in the range of 0°C to 40°C, and optimizes material performance through dynamic viscoelastic measurement.

Benefits of technology

It achieves excellent vibration suppression effect on uneven or curved surfaces, and improves the follow-up nature and vibration control performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627577000001
    Figure 0007627577000001
Patent Text Reader

Abstract

To provide a damping material that has excellent damping properties and has excellent followability to an irregular or curved surface.SOLUTION: A damping material has a resin layer (1), and a constraint layer (2) laminated on the resin layer (1). The resin layer (1) is composed of foam of an olefin polymer (A). The foam has at least one peak of loss tangent tanδ by dynamic viscoelasticity measurement in a temperature range of 0°C or higher and 40°C or lower.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a vibration-damping material. [Background technology]

[0002] Parts and housings used in fields such as automobiles, ships, railway vehicles, aircraft, home electrical appliances, OA equipment, AV equipment, office equipment, building and housing facilities, machine tools, and industrial machinery are prone to vibration and noise during operation, and require vibration damping to suppress the generation of vibration and noise. It is known to attach vibration damping materials to the parts and housings in order to improve the vibration damping of the above-mentioned parts and housings.

[0003] For example, Patent Document 1 describes a vibration-damping material having a vibration-damping resin layer made of a vibration-damping resin composition containing chlorinated polyethylene. Patent Documents 2 and 3 describe a vibration-damping sheet having a vibration-damping layer containing butyl rubber. Patent Document 4 describes an adhesive sheet that can be used for vibration damping of steel plates, in which an epoxy resin foam is used in the resin layer.

[0004] On the other hand, Patent Document 5 describes a composite including a foam made of a 4-methyl-1-pentene polymer, the foam having a temperature at which the loss tangent (tan δ) obtained by dynamic viscoelasticity measurement shows a maximum value and the maximum value identified, and a member bonded to the foam and different from the foam. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2006-125150 A [Patent Document 2] Japanese Patent Application Publication No. 09-136998 [Patent Document 3] JP 2013-181155 A [Patent Document 4] JP 2005-53014 A [Patent Document 5] International Publication No. 2018 / 143411 Summary of the Invention [Problem to be solved by the invention]

[0006] Conventional constrained vibration-damping materials, in which a constraining layer such as a metal foil is laminated to a resin layer, had room for improvement in terms of their ability to conform to the surface when they are attached to the uneven or curved surface of the component to be damped. The present invention provides a vibration-damping material that has excellent vibration-damping properties and excellent conformability to a surface that has irregularities or is curved. [Means for solving the problem]

[0007] As a result of investigations aimed at solving the above problems, the inventors have found that the above problems can be solved by the vibration-damping material described below, and have thus completed the present invention. The present invention relates to, for example, the following [1] to [7].

[0008] [1] The present invention comprises a resin layer (1) and a constraining layer (2) laminated on the resin layer (1), the resin layer (1) is made of a foam of an olefin-based polymer (A), The foam has one or more peaks of loss tangent tan δ determined by dynamic viscoelasticity measurement in a temperature range of 0° C. or higher and 40° C. or lower. [2] The vibration-damping material according to [1], wherein the resin layer (1) has a thickness of 0.1 mm or more and 10 mm or less. [3] The vibration-damping material according to [1] or [2], wherein the thickness of the constraining layer (2) is 0.06 mm or more and 12 mm or less. [4] The vibration damping material according to any of the above [1] to [3], wherein the olefin polymer (A) is a copolymer (A-1) having a content of structural units (i) derived from 4-methyl-1-pentene of 16 to 95 mol %, a content of structural units (ii) derived from an α-olefin having 2 to 20 carbon atoms excluding 4-methyl-1-pentene of 5 to 84 mol %, and a content of structural units (iii) derived from a non-conjugated polyene of 0 to 10 mol % (wherein the total content of structural units (i), (ii), and (iii) is 100 mol %). [5] The vibration damping material according to [4], wherein the α-olefin having 2 to 20 carbon atoms is propylene. [6] The vibration-damping material according to any one of the above [1] to [5], wherein the constraining layer (2) is selected from a metal plate, a metal mesh, a resin layer, a fiber-reinforced resin layer, and a glass cloth. [7] The vibration-damping material according to [6], wherein the constraint layer (2) is an aluminum plate. Effect of the Invention

[0009] According to the present invention, there is provided a vibration-damping material that has excellent vibration-damping properties and excellent conformability to a surface that has irregularities or is curved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The vibration damping material of the present invention is The present invention comprises a resin layer (1) and a constraining layer (2) laminated on the resin layer (1), the resin layer (1) is made of a foam of an olefin-based polymer (A), The foam has at least one peak of loss tangent tanδ determined by dynamic viscoelasticity measurement in a temperature range of 0° C. to 40° C. It is characterized by the following.

[0011] [Resin layer (1)] The resin layer (1) is made of a foam of an olefin polymer (A) having at least one peak of loss tangent tan δ determined by dynamic viscoelasticity measurement in the temperature range of 0° C. or higher and 40° C. or lower.

[0012] <Foam of Olefin Polymer (A)> From the viewpoint of obtaining a high vibration damping effect mainly around room temperature, the foam of the olefin polymer (A) has one or more peaks of loss tangent tan δ determined by dynamic viscoelasticity measurement in the temperature range of 0° C. to 40° C. From the viewpoint of further improving the vibration damping property of the obtained vibration damping material, the foam preferably has one or more peaks of the tan δ in the temperature range of 10° C. to 40° C.

[0013] The loss tangent tanδ will be described. For a sample made of a foam of an olefin polymer (A), dynamic viscoelasticity measurement is performed while continuously changing the ambient temperature, the storage modulus (G') and loss modulus (G") are measured, and the loss tangent tanδ given by G" / G' is calculated. Looking at the relationship between temperature and loss tangent tanδ, the loss tangent tanδ generally has a peak at a specific temperature. The temperature at which the peak appears is generally called the glass transition temperature (hereinafter also referred to as "tanδ-Tg"). The temperature at which the peak of the loss tangent tanδ appears can be calculated based on the dynamic viscoelasticity measurement described in the examples (a foam is cut into a rectangular shape of 30 mm length x 10 mm width, and dynamic viscoelasticity in the temperature range of 0°C to 110°C under the conditions of a chuck distance of 20 mm, a frequency of 1.59 Hz, a distortion amount of 0.1%, a heating rate of 4°C / min, and a twisting mode).

[0014] The value of the loss tangent tan δ at the peak, ie, the maximum value, is preferably 0.8 to 3.0. The presence or absence of a peak of tan δ in the temperature range of 0° C. or more and 40° C. or less is judged based on whether or not the apex of the peak of tan δ exists in the temperature range of 0° C. or more and 40° C. or less.

[0015] A foam of the olefin polymer (A) having one or more tan δ peaks in the above temperature range can be obtained, for example, by adjusting the composition ratio of the structural units (i) to (iii) of the olefin polymer (A) described below.

[0016] The intrinsic viscosity [η] of the olefin polymer (A) in decalin at 135° C. is preferably 0.5 dL / g or more, more preferably 0.6 dL / g or more, even more preferably 0.7 dL / g or more, and is preferably 5.0 dL / g or less, more preferably 4.0 dL / g or less, and even more preferably 3.5 dL / g or less, from the viewpoint of processability. The method of adjusting the intrinsic viscosity [η] is not particularly limited, but the intrinsic viscosity [η] can be adjusted by adjusting the molecular weight of the olefin polymer (A) by using hydrogen molecules in combination during polymerization.

[0017] The molecular weight distribution (Mw / Mn), which is the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the olefin polymer (A), is preferably 3.5 or less, more preferably 3.0 or less, and even more preferably 2.5 or less, and is preferably 1.2 or more, and more preferably 1.5 or more, from the viewpoint of the mechanical properties and processability of the obtained vibration damping material. Mw and Mn are obtained by using gel permeation chromatography (GPC) and a standard polystyrene conversion method.

[0018] The olefin polymer (A) is a polymer formed from one or more olefins, and may be a homopolymer or a copolymer. Examples of the olefin include α-olefins, cyclic olefins, aromatic vinyl compounds, and functionalized vinyl compounds.

[0019] Examples of the α-olefin include linear or branched α-olefins. The number of carbon atoms in the α-olefin is not particularly limited, but is preferably 2 to 20. The number of carbon atoms in the linear α-olefin is preferably 2 to 20, more preferably 2 to 15, and further preferably 2 to 10. Examples of the linear α-olefin include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene, and preferably ethylene, propylene, 1-butene, 1-pentene, 1-hexene, and 1-octene.

[0020] The number of carbon atoms in the branched α-olefin is preferably 5 to 20, more preferably 5 to 15. Examples of the branched α-olefin include 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3-ethyl-1-pentene, 4,4-dimethyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4-ethyl-1-hexene, and 3-ethyl-1-hexene.

[0021] The number of carbon atoms in the cyclic olefin is preferably 3 to 20, more preferably 5 to 15. Examples of the cyclic olefin include cyclopentene, cyclohexene, cycloheptene, norbornene, 5-methyl-2-norbornene, tetracyclododecene, and vinylcyclohexane.

[0022] Examples of aromatic vinyl compounds include mono- or polyalkylstyrenes such as styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, o,p-dimethylstyrene, o-ethylstyrene, m-ethylstyrene, and p-ethylstyrene.

[0023] Examples of functionalized vinyl compounds include hydroxyl group-containing olefins; unsaturated carboxylic acids such as (meth)acrylic acid, propionic acid, 3-butenoic acid, 4-pentenoic acid, 5-hexenoic acid, 6-heptenoic acid, 7-octenoic acid, 8-nonenoic acid, 9-decenoic acid, and 10-undecenoic acid; unsaturated amines such as allylamine, 5-hexenamine, and 6-heptenamine; (2,7-octadienyl)succinic anhydride, pentapropenylsuccinic anhydride, and anhydrides obtained from the above unsaturated carboxylic acids. unsaturated carboxylic acid anhydrides such as 4-epoxy-1-butene, 5-epoxy-1-pentene, 6-epoxy-1-hexene, 7-epoxy-1-heptene, 8-epoxy-1-octene, 9-epoxy-1-nonene, 10-epoxy-1-decene, and 11-epoxy-1-undecene; and ethylenically unsaturated silane compounds such as vinyltrimethoxysilane, vinyltriethoxysilane, and γ-(meth)acryloxypropyltrimethoxysilane.

[0024] Examples of hydroxyl-containing olefins include terminally hydroxylated olefins. Examples of terminally hydroxylated olefins include linear hydroxylated α-olefins having 2 to 20 carbon atoms, preferably 2 to 15 carbon atoms, such as vinyl alcohol, allyl alcohol, 1-butene hydroxide, 1-pentene hydroxide, 1-hexene hydroxide, 1-octene hydroxide, 1-decene hydroxide, 1-undecene hydroxide, 1-dodecene hydroxide, 1-tetradecene hydroxide, 1-hexadecene hydroxide, 1-octadecene hydroxide, and 1-eicosene hydroxide. branched hydroxylated α-olefins having 5 to 20 carbon atoms, preferably 5 to 15 carbon atoms, such as 3-methyl-1-butene hydroxide, 3-methyl-1-pentene hydroxide, 4-methyl-1-pentene hydroxide, 3-ethyl-1-pentene hydroxide, 4,4-dimethyl-1-pentene hydroxide, 4-methyl-1-hexene hydroxide, 4,4-dimethyl-1-hexene hydroxide, 4-ethyl-1-hexene hydroxide, and 3-ethyl-1-hexene hydroxide.

[0025] As the monomer for forming the olefin polymer (A), at least one selected from non-conjugated polyenes and conjugated dienes can be used together with the above-mentioned olefins. The number of carbon atoms of the non-conjugated polyene is preferably 5 to 20, more preferably 5 to 10. Examples of the non-conjugated polyene include 1,4-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 1,4-octadiene, 1,5-octadiene, 1,6-octadiene, 1,7-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, 7-methyl-1,6-octadiene, 4-ethylidene-8-methyl-1,7-nonadiene, 4,8-dimethyl-1,4,8-decatriene, and dicyclopentadiene. Examples of such norbornene include butyl norbornene, ...

[0026] The number of carbon atoms of the conjugated diene is preferably 4 to 20, more preferably 4 to 10. Examples of the conjugated diene include 1,3-butadiene, isoprene, 1,3-pentadiene, 2,3-dimethylbutadiene, 4-methyl-1,3-pentadiene, 1,3-hexadiene, and 1,3-octadiene.

[0027] The olefin polymer (A) is preferably a non-halogenated olefin polymer from the viewpoint of low pollution (low pollution) to workers and the working environment. From the viewpoint of facilitating the production of a copolymer having one or more peaks of loss tangent tanδ in the vicinity of 0 to 40° C., the olefin polymer (A) preferably contains a copolymer (A-1) having a structural unit (i) derived from 4-methyl-1-pentene and a structural unit (ii) derived from an α-olefin having 2 to 20 carbon atoms other than 4-methyl-1-pentene.

[0028] The α-olefin having 2 to 20 carbon atoms in the copolymer (A-1) is preferably a linear α-olefin having 2 to 10 carbon atoms, more preferably ethylene, propylene, 1-butene, 1-pentene, 1-hexene and 1-octene, more preferably ethylene and propylene, particularly preferably propylene. The structural unit (ii) in the copolymer (A-1) may be one type or a combination of two or more types.

[0029] The copolymer (A-1) may contain a structural unit (iii) derived from a non-conjugated polyene, if necessary. The structural unit (iii) in the copolymer (A-1) may be one type or a combination of two or more types.

[0030] Copolymer (A-1) may have a structural unit derived from other copolymer components within the scope of the present invention. Examples of other copolymer components include the above-mentioned cyclic olefins, aromatic vinyl compounds, functionalized vinyl compounds, and conjugated dienes.

[0031] In the copolymer (A-1), the total content of the structural units (i), (ii) and (iii) is taken as 100 mol%, and it is preferable that the content of the structural unit (i) is 16 to 95 mol%, the content of the structural unit (ii) is 5 to 84 mol%, and the content of the structural unit (iii) is 0 to 10 mol%, it is more preferable that the content of the structural unit (i) is 26 to 90 mol%, the content of the structural unit (ii) is 10 to 74 mol%, and the content of the structural unit (iii) is 0 to 7 mol%, and it is even more preferable that the content of the structural unit (i) is 61 to 85 mol%, the content of the structural unit (ii) is 15 to 39 mol%, and the content of the structural unit (iii) is 0 to 5 mol%. The above content ratios are 13 It can be measured by C-NMR.

[0032] The olefin polymer (A) can be produced by a conventional method using a polymerization catalyst such as a metallocene catalyst, for example, as described in WO 2011 / 055803 and WO 2005 / 121192. The olefin polymer (A) can be used alone or in combination.

[0033] (Optional Additives) The foam of the olefin polymer (A) may contain additives such as heat stabilizers, antioxidants, ultraviolet absorbers, pigments, antistatic agents, copper damage inhibitors, flame retardants, neutralizing agents, plasticizers, nucleating agents, bubble inhibitors, weather stabilizers, light stabilizers, antiaging agents, fatty acid metal salts, softeners, dispersants, colorants, lubricants, natural oils, synthetic oils, waxes, and polymers other than the olefin polymer (A), as necessary, within the range that does not impair the effects of the present invention.

[0034] <Method for producing resin layer (1)> The resin layer (1) made of a foam of the olefin polymer (A) can be obtained, for example, by foam-molding the olefin polymer (A) or a mixture of the olefin polymer (A) and additives into a sheet.

[0035] The molding apparatus and molding conditions are not particularly limited, and conventionally known molding apparatus and molding conditions can be used, but molding using an extrusion molding apparatus is preferred. The foaming agent used in producing the foam of the olefin polymer (A) includes a chemical foaming agent and a physical foaming agent, which may be used alone or in combination.

[0036] Examples of chemical foaming agents include sodium bicarbonate, ammonium bicarbonate, various carboxylates, sodium borohydride, azodicarboxamide, N,N-dinitrosopentamethylenetetramine, P,P-oxybis(benzenesulfonyl hydrazide), azobisisobutyronitrile, paratoluenesulfonyl hydrazide, sodium bicarbonate, and sodium citrate.

[0037] The physical foaming agent may be carbon dioxide, nitrogen, or a mixture of carbon dioxide and nitrogen, any of which may be supplied in a gaseous, liquid or supercritical state. The chemical foaming agent is preferably mixed uniformly with the olefin polymer (A) before being charged into the extruder.

[0038] When carbon dioxide is used as a physical foaming agent, it is preferred that the olefin polymer (A) is kneaded and plasticized in the extruder, and then the carbon dioxide is directly injected into the extruder. The expansion ratio of the olefin polymer (A) is not particularly limited, and can be appropriately determined in consideration of various physical properties of the resulting foam.

[0039] [Restricted layer (2)] The constraining layer (2) constrains the resin layer (1) and imparts toughness to the resin layer (1). In one embodiment, the constraining layer (2) is laminated on the resin layer (1) to enhance the effect as a vibration-damping material. The constraining layer (2) is, for example, a sheet-like layer that can be closely attached and integrated with the resin layer (1).

[0040] Examples of the constraining layer (2) include a metal plate, a metal mesh, a resin layer, a fiber-reinforced resin layer, and a glass cloth. Examples of the metal plate include an aluminum plate, a steel plate, a stainless steel plate, a nickel plate, and a copper plate.

[0041] The metal mesh is a metal material that has been woven in a plain weave, twill weave, plain tatami weave, twill tatami weave, etc., and examples thereof include stainless steel mesh (stainless steel wire mesh). The metal mesh may also be a resin-impregnated metal mesh that has been impregnated with a synthetic resin such as a thermosetting resin or a thermoplastic resin. Examples of the thermosetting resin include an epoxy resin, a urethane resin, a melamine resin, and a phenolic resin. Examples of the thermoplastic resin include a vinyl acetate resin, an ethylene-vinyl acetate copolymer (EVA), a polyvinyl chloride resin (PVC), various polyamide resins, various polyolefin resins, and various polyester resins. These thermosetting resins and thermoplastic resins may each be used alone or in combination of two or more kinds.

[0042] Examples of the resin for forming the resin layer include thermoplastic resins and thermosetting resins. Examples of the thermoplastic resin include various polyesters such as polyethylene terephthalate (PET), various polyamides such as nylon 6 (polyamide 6), various polyolefin resins such as polyethylene and polypropylene, various (meth)acrylic resins such as polymethyl (meth)acrylate, vinyl acetate resin, ethylene-vinyl acetate copolymer (EVA), and polyvinyl chloride resin (PVC). Examples of the thermosetting resin include epoxy resin, phenol resin, and urethane resin. The resin may also be a foam, and examples of the foam include foamed polyethylene, foamed polypropylene, and foamed ethylene-vinyl acetate copolymer, which are foamed thermoplastic resins, and urethane foam, which is foamed thermosetting resins. The resin layer as the constraining layer (2) is a layer formed from a resin different from the above-mentioned resin layer (1).

[0043] Examples of the fiber reinforced resin for forming the fiber reinforced resin layer include various types of glass fiber reinforced resin (FRP) and carbon fiber reinforced resin (CFRP), and known fiber reinforced resins are included.

[0044] The glass cloth is a cloth made of glass fibers, and examples thereof include known ones. The glass cloth may have an adhesive attached to its surface. The glass cloth may be a resin-impregnated glass cloth impregnated with a synthetic resin such as a thermosetting resin or a thermoplastic resin. Examples of the thermosetting resin include an epoxy resin, a urethane resin, a melamine resin, and a phenol resin. Examples of the thermoplastic resin include a vinyl acetate resin, an ethylene-vinyl acetate copolymer (EVA), a polyvinyl chloride resin (PVC), various polyamide resins, various polyolefin resins, and various polyester resins. These thermosetting resins and thermoplastic resins may each be used alone or in combination of two or more kinds.

[0045] Of the constraining layers (2), from the viewpoints of vibration-damping properties, processability, and cost, metal plates, metal meshes, resin layers, and glass cloth are preferred, metal plates, resin layers, and glass cloth are more preferred, metal plates are even more preferred, and aluminum plates are particularly preferred.

[0046] From the viewpoints of vibration damping, workability, and unevenness-following ability, the thickness of the constraining layer (2) is preferably 0.06 mm or more, more preferably 0.5 mm or more, even more preferably 1.2 mm or more, even more preferably 2 mm or more, and is preferably 12 mm or less, more preferably 10 mm or less, and even more preferably 8 mm or less. Since the resin layer of the vibration damping material of the present invention is made of the above-mentioned foam, even if the constraining layer is relatively thick, it exhibits excellent unevenness-following ability compared to vibration damping materials whose resin layer is not a foam.

[0047] [Other layers] In addition to the resin layer (1) and the constraining layer (2), the vibration-damping material of the present invention may have a known release paper or release film, if necessary, on the surface of the resin layer (1) opposite to the surface on which the constraining layer (2) is laminated. In that case, it is preferable that the release paper or release film is laminated on the resin layer (1) when the resin layer (1) is formed into a sheet.

[0048] <Method of manufacturing vibration-damping material> The vibration-damping material of the present invention can be produced by various known methods, such as a method in which the resin layer (1) is obtained using an apparatus such as a press or an extruder, and then, if necessary, a constraining layer (2) is pressure-bonded or thermocompression-bonded to the resin layer (1), or a method in which an olefin-based polymer (A) or a mixture of the olefin-based polymer (A) and an additive is extrusion-laminated on the surface of the constraining layer (2) using an apparatus such as an extruder, to form the resin layer (1) on the constraining layer (2).

[0049] <Applications of vibration damping materials> The vibration-damping material of the present invention is attached to a member (for example, a part or a housing) to be subjected to vibration damping, and damps the vibration of the part or the housing.

[0050] For this reason, the vibration-damping material can be used for parts or housings in a variety of applications where vibrations occur, such as automobiles, ships, railway vehicles, aircraft, household electrical appliances, office equipment, AV equipment, office machinery, building and housing facilities, machine tools, and industrial machinery. The vibration-damping material is suitable for use in clean rooms and the like because it is less polluting to workers and the working environment. It can be used in clean rooms and the like, where vibrations are generated, such as liquid crystal panel manufacturing equipment, plasma panel manufacturing equipment, semiconductor panel manufacturing equipment, organic EL panel manufacturing equipment, silicon wafer manufacturing equipment, mobile phone manufacturing equipment, touch panel manufacturing equipment, printed circuit board manufacturing equipment, coating equipment, polarizing film extruders, polarizing film winding machines, optical film extruders, optical film winding machines, cutting machines, laser micromachining equipment, ultrasonic processing equipment, semiconductor exposure equipment, liquid crystal exposure equipment, X-ray inspection equipment, pharmaceutical manufacturing equipment, pesticide manufacturing equipment, homogenizers, mixers, presses, clean benches, air showers, belt conveyors, air conditioning equipment, product manufacturing machines, product filling machines, packaging printing machines, cleaning machines, scanning electron microscopes, transmission electron microscopes, film thickness measuring machines, etching equipment, film formation equipment, LED substrate manufacturing equipment, vacuum dryers, inert ovens, high-temperature furnaces, polishers, and other manufacturing sites for semiconductors, liquid crystals, food, cosmetics, pharmaceuticals, and the like.

[0051] For example, when the vibration-damping material has a release paper or a release film on the surface of the resin layer (1), the release paper or the release film is peeled off from the surface of the resin layer (1) during use, and then the surface of the resin layer (1) is attached to the adherend, which is the object to be damped (various parts, housing, etc.). The vibration-damping material of the present invention can be attached to the object to be damped by, for example, pressing or thermocompression bonding (baking) the resin layer (1) and the object to be damped (various parts, housing, etc.). EXAMPLES

[0052] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0053] [Measurement and evaluation methods] In the following examples, measurements and evaluations were carried out by the following methods.

[0054] <Polymer analysis> [composition] The mole fraction (mol%) of each structural unit of the olefin copolymer is: 13 The measured values ​​were obtained by C-NMR. The measured values ​​were obtained by using an ECX400P nuclear magnetic resonance apparatus (manufactured by JEOL Ltd.) at a measurement temperature of 120°C, a measurement solvent of orthodichlorobenzene / deuterated benzene = 4 / 1, and an accumulation number of 8000 times. 13 The C-NMR spectrum was obtained.

[0055] [Intrinsic viscosity] The intrinsic viscosity [η] of the olefin polymer was measured in decalin solvent at 135° C. using an Ubbelohde viscometer as a measuring device. Specifically, about 20 mg of powdered polymer was dissolved in 25 mL of decalin, and the specific viscosity η was measured using an Ubbelohde viscometer in an oil bath at 135° C. SP The decalin solution was diluted with 5 mL of decalin, and the specific viscosity η was measured in the same manner as above. SP This dilution procedure was repeated twice, and the η SPThe value of / C was calculated as the intrinsic viscosity [η] (unit: dL / g) (see formula 1 below). [η]=lim(η SP / C) (C→0) ···Equation 1

[0056] [Weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn)] The weight average molecular weight (Mw) of the olefin polymer and the molecular weight distribution (Mw / Mn) expressed as the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) were calculated by gel permeation chromatography (GPC) using a standard polystyrene conversion method. The measurement conditions are as follows. Measuring device: GPC (ALC / GPC 150-C plus type, (Differential refractometer with integrated detector, Waters) Column: 2 GMH6-HT and 2 GMH-HTL connected in series (All manufactured by Tosoh Corporation) Eluent: o-dichlorobenzene Column temperature: 140℃ Flow rate: 1.0mL / min

[0057] [Dynamic viscoelasticity] The resin layer used in the examples was cut into a rectangular shape of 30 mm long x 10 mm wide to prepare a test piece. Next, using MC301 manufactured by Anton Paar, the temperature dependency of dynamic viscoelasticity was measured in the temperature range of 0°C to 110°C under the conditions of chuck distance of 20 mm, frequency of 1.59 Hz, strain of 0.1%, heating rate of 4°C / min, and twisting mode. From the obtained graph, the temperature at which the peak of loss tangent (tanδ) due to the glass transition point in the temperature range appears, that is, the temperature showing the maximum value of loss tangent (tanδ) (glass transition temperature: Tg) and the maximum value of tanδ were obtained.

[0058] <Evaluation of vibration-damping materials> [Unevenness tracking ability] A 1mm high convex portion was created on an aluminum plate measuring 100mm long x 300mm wide x 3mm thick, and the resin layer side of a 100mm long x 200mm wide vibration-damping material was pressed against the plate using a pressure roller. The vibration-damping material's ability to conform to the uneven surface was then evaluated visually. The symbols in Table 1 have the following meanings: ○: No peeling from the aluminum plate ×: Some parts peeled off from the aluminum plate

[0059] [Vibration Damping] The resin layer side of the vibration-damping material, 100 mm long x 300 mm wide, was pressed against the center of an aluminum substrate (adherend) 100 mm wide x 600 mm long x 40 mm thick to prepare a test specimen. The substrate was vibrated with an impact hammer (PCB), the acceleration was detected with an acceleration pickup (PCB), and measured with an FFT analyzer (OROS), to measure the vibration acceleration level of the substrate. At the resonance frequency of the obtained frequency response function (accelerance: A / F), the peak value of the vibration acceleration level near 500 Hz was compared with the case of only the substrate to determine the reduction amount. The greater the reduction amount of the peak value of the vibration acceleration level, the better the vibration damping performance.

[0060] The following criteria were evaluated on a scale of 1 to 3. 0dB to less than 6dB decrease = 1 point 6~12dB reduction = 2 points >12dB decrease = 3 points

[0061] (Polymer production) [Polymerization Example 1] A 1.5-liter stainless steel autoclave equipped with an agitator and thoroughly purged with nitrogen was charged with 300 ml of normal hexane (dried over activated alumina in a dry nitrogen atmosphere) and 450 ml of 4-methyl-1-pentene at 23° C. 0.75 ml of a 1.0 mmol / ml toluene solution of triisobutylaluminum (TIBAL) was charged into the autoclave, and the agitator was turned on.

[0062] Next, the autoclave was heated to an internal temperature of 60°C, and pressurized with propylene so that the total pressure was 0.40MPa (gauge pressure). Then, 0.34ml of a toluene solution containing 1mmol of methylaluminoxane in terms of Al and 0.01mmol of diphenylmethylene (1-ethyl-3-t-butyl-cyclopentadienyl) (2,7-di-t-butyl-fluorenyl) zirconium dichloride, which had been prepared in advance, was pressed into the autoclave with nitrogen to start polymerization. During the polymerization reaction, the temperature was adjusted so that the internal temperature of the autoclave was 60°C. 60 minutes after the start of polymerization, 5ml of methanol was pressed into the autoclave with nitrogen to stop the polymerization, and the autoclave was depressurized to atmospheric pressure. Acetone was poured into the reaction solution while stirring.

[0063] The resulting solvent-containing polymer was dried at 100°C under reduced pressure for 12 hours to obtain 4-methyl-1-pentene copolymer (A-1). The content of structural units derived from 4-methyl-1-pentene in copolymer (A-1) was 72 mol%, and the content of structural units derived from propylene was 28 mol%. The intrinsic viscosity [η] of copolymer (A-1) in decalin at 135°C was 1.5 dL / g, the weight average molecular weight (Mw) was 337,000, the molecular weight distribution (Mw / Mn) was 2.1, the tanδ-Tg was 28°C, and the maximum value of tanδ was 2.8.

[0064] (Manufacturing of resin sheets) [Production Example 1] The molding machine used consisted of a single-screw extruder (cylinder inner diameter D: 50 mm, full-flight screw, L / D: 32 mm when L is the effective screw length, carbon dioxide supply position: 17.5 D from the screw supply side), a T-die (die width: 320 mm, lip opening: 0.5 to 1.8 mm), a cooling roll (outer diameter 50 mm, made of steel with mirror-finished hard chrome plating surface treatment, water-cooled), a carbon dioxide supply device, a cooling roll, and a take-up machine.

[0065] First, 100 parts by mass of the 4-methyl-1-pentene copolymer (A-1) obtained in Polymerization Example 1 and 0.3 parts by mass of a blowing agent (sodium bicarbonate, sodium citrate (Otsuka Chemical Co., Ltd.)) were dry-blended, and the resulting mixture was charged into a hopper. Further, carbon dioxide was injected from a carbon dioxide supplying device into the middle of the cylinder of the extruder (position 17.5D) at a pressure of 10 to 23 MPa. The amount of carbon dioxide injected was adjusted to be 0.1 to 0.8% by mass with respect to the extrusion amount. The raw materials were melted and kneaded under conditions of a temperature of 100-230°C in each part of the cylinder and a screw rotation speed of 20-36 rpm, and extruded from a T-die so as to give an extrusion rate of 5-8.5 kg / hr at a resin temperature of 130-195°C in the cylinder head. The extruded foam sheet was cooled with a cooling roll (water passing temperature inside the roll: 30°C) and taken up with a take-up machine (take-up speed: 0.4-2.3 m / min) to obtain a foam (sheet-shaped resin layer (1)) having a sheet width of about 300 mm and a thickness of 0.5 mm.

[0066] [Production Example 2] The 4-methyl-1-pentene copolymer (A-1) obtained in Polymerization Example 1 was heated at 190° C. for 5 minutes using a hot press, and then cooled and pressed to obtain a sheet-like resin layer (2) having a thickness of 0.5 mm.

[0067] (Manufacturing of vibration-damping materials) [Example 1] An aluminum plate having a thickness of 0.2 mm was attached as a constraining layer to one surface of the foam obtained in Production Example 1 (sheet-shaped resin layer (1), hereinafter also referred to as "4MP-1 copolymer foam") by pressure bonding, thereby obtaining a vibration damping material having a total thickness of 0.7 mm for the resin layer and the constraining layer. This vibration-damping material was evaluated, and the results are shown in Table 1.

[0068] [Examples 2 to 5] A vibration damping material was produced and evaluated in the same manner as in Example 1, except that the aluminum plate was changed to one with a thickness shown in Table 1. The results are shown in Table 1.

[0069] [Comparative Example 1] A vibration-damping material was produced and evaluated in the same manner as in Example 1, except that an aluminum plate was not used as the constraining layer, and only a 0.5 mm-thick sheet-shaped resin layer was used as the vibration-damping material. The results are shown in Table 1.

[0070] [Comparative Example 2] A vibration damping material was produced and evaluated in the same manner as in Example 1, except that the sheet-shaped resin layer (1) was changed to the sheet-shaped resin layer (2) (hereinafter also referred to as "4MP-1 copolymer") produced in Production Example 2. The results are shown in Table 1.

[0071] [Comparative Example 3] Evaluation was performed in the same manner as in Example 1, except that the sheet-like resin layer (1) was changed to a polyethylene foamed sheet (Hisheet (registered trademark), manufactured by Mitsui Chemicals Tocello Co., Ltd., Tg is a typical value for polyethylene, hereinafter also referred to as "foamed PE"). The results are shown in Table 1.

[0072] [Table 1]

Claims

1. The present invention comprises a resin layer (1) and a constraining layer (2) laminated on the resin layer (1), the resin layer (1) is made of a foam of an olefin-based polymer (A), The foam has one or more peaks of loss tangent tanδ determined by dynamic viscoelasticity measurement in a temperature range of 0° C. or more and 40° C. or less; The thickness of the constraint layer (2) is 1.2 mm or more and 12 mm or less, The olefin polymer (A) includes a copolymer (A-1) having a structural unit (i) derived from 4-methyl-1-pentene and a structural unit (ii) derived from an α-olefin having 2 to 20 carbon atoms excluding 4-methyl-1-pentene. Damping material.

2. 2. The vibration damping material according to claim 1, wherein the resin layer (1) has a thickness of 0.1 mm or more and 10 mm or less.

3. The vibration damping material according to claim 1 or 2, wherein the olefin polymer (A) is a copolymer (A-1) having a content of structural units (i) derived from 4-methyl-1-pentene of 16 to 95 mol %, a content of structural units (ii) derived from an α-olefin having 2 to 20 carbon atoms excluding 4-methyl-1-pentene of 5 to 84 mol %, and a content of structural units (iii) derived from a non-conjugated polyene of 0 to 10 mol % (wherein the total content of structural units (i), (ii) and (iii) is 100 mol %).

4. 4. The vibration damping material according to claim 3, wherein the α-olefin having 2 to 20 carbon atoms is propylene.

5. The vibration damping material according to any one of claims 1 to 4, wherein the constraining layer (2) is selected from a metal plate, a metal mesh, a resin layer, a fiber-reinforced resin layer, and a glass cloth.

6. 6. The vibration damping material according to claim 5, wherein the constraining layer (2) is an aluminum plate.

Citation Information

Patent Citations

  • High-temperature vibration damper material and vibration damper sheet

    JP1997136998A

  • Laminating sheet for steel sheet

    JP2005053014A

  • Restricted damping material

    JP2006125150A

  • Damping sheet for automobile

    JP2009241486A

  • Damping sheet for automobile

    JP2009243614A